2013
DOI: 10.1037/a0028732
|View full text |Cite
|
Sign up to set email alerts
|

Binding of intrinsic and extrinsic features in working memory.

Abstract: There is ongoing debate concerning the mechanisms of feature binding in working memory. In particular, there is controversy regarding the extent to which these binding processes are automatic. The present article demonstrates that binding mechanisms differ depending on whether the to-be-integrated features are perceived as forming a coherent object. We presented a series of experiments that investigated the binding of color and shape, whereby color was either an intrinsic feature of the shape or an extrinsic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
106
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 136 publications
(228 reference statements)
21
106
2
2
Order By: Relevance
“…Supporting evidence also comes from the observation that younger children produced a higher rate of inappropriate feature pairings in the presence of correct feature memory. Unlike tasks used in previous research, the binding between visual form and novel auditory-verbal information explored in the current study likely reflects a particular form of extrinsic or relational binding (Ecker et al, 2013;Parra et al, 2013) that relies more heavily on the active formation of new associations between modalities within a working memory storage component such as the episodic buffer (Baddeley, 2000(Baddeley, , 2012Baddeley et al, 2011). The current findings that these processes show a particular developmental trajectory and are separable from those shown in working memory for the constituent visual and auditory-verbal elements therefore provides novel evidence for maturation of processes associated with the episodic buffer.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Supporting evidence also comes from the observation that younger children produced a higher rate of inappropriate feature pairings in the presence of correct feature memory. Unlike tasks used in previous research, the binding between visual form and novel auditory-verbal information explored in the current study likely reflects a particular form of extrinsic or relational binding (Ecker et al, 2013;Parra et al, 2013) that relies more heavily on the active formation of new associations between modalities within a working memory storage component such as the episodic buffer (Baddeley, 2000(Baddeley, , 2012Baddeley et al, 2011). The current findings that these processes show a particular developmental trajectory and are separable from those shown in working memory for the constituent visual and auditory-verbal elements therefore provides novel evidence for maturation of processes associated with the episodic buffer.…”
Section: Discussionmentioning
confidence: 75%
“…of shape and color within an object) may be relatively low-level and perceptual in nature, possibly accomplished by specialized visuospatial processing before being consciously retained within the episodic buffer. In contrast, relational or extrinsic binding (Ecker, Maybery, & Zimmer, 2013;Parra et al, 2013) of elements from different domains or modalities may particularly require the episodic buffer for their formation and retention, as implied by BaddeleyÕs original (2000) proposal. Therefore, for current purposes, episodic buffer capacity was indexed by a task in which temporary creation and maintenance of bound visual and phonological information were needed.…”
mentioning
confidence: 99%
“…As suggested by Baddeley et al (2011), these bindings could be too basic and automatic to be affected by concurrent cognitive load. A recent study by Ecker, Maybery, and Zimmer (2013) has suggested a difference in the automacity of binding based on the perceived coherence of the to-be-bound features. Features that are perceived as belonging to a same object are defined as intrinsically related (e.g., color and shape) and resulted in an obligatory and automatic binding and retrieval of the binding.…”
Section: Methodsmentioning
confidence: 99%
“…Ecker et al, 2013;Parra et al, 2013;Zimmer et al, 2006). Thus, the integration of elements for different types of social category conjunction might represent one example of a wider set of differences between automatic and more effortful binding processes.…”
Section: The Revised Novel Conjunctive Compatibility Two-stage Modelmentioning
confidence: 99%